TRADISI MERANTAU DALAM CERITA RAKYAT SUNDA NYI MAS KANTI Kajian Strukturalisme Naratif Levis-Strauss - Agatha Trisari S; Hanny Harashani (Media Bahasa, Sastra, dan Budaya Wahana, 2018)
AbstractThe structures of Levi-Strauss Naratif were used to study the intrinsic aspect of Folktales. Folktale Nyi Mas Kanti were studied using the manners of Levi-Strauss Naratif. The flow scheme of the plot is achieved in this order, including: parting, moving, and encountering.The flow of the story that leads into Moving is actually inline with the basic concept of Merantauwhich is known as an act of going away from home for a long timeto persue success,glory,knowledge,or wealth.From the explanation above we can conclude that Merantau is a social foundation in the specific culture which is Indonesia and it is already been done since centuries ago.These folktales is part of the Indonesian Written Legacy that passed down to the next generation collectively using methods of Merantau as the flow of the story inside the Folktales, intentional or not.Key words : strukturalisme naratif, mytheme, scheme, moving, merantau